2004
DOI: 10.1007/s10811-004-5504-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characterisation and differentiation of Sargassum baccularia and S. polycystum (Phaeophyta)

Abstract: Two Sargassum species (S. baccularia and S. polycystum) collected from Teluk Kemang and Cape Rachado, Port Dickson, Negeri Sembilan, Malaysia, which are alike in morphology except for the rhizoidal system and vesicles, were characterised using random amplified polymorphism DNA (RAPD). The genomic DNA of both species was isolated from the leaves using a modified CTAB method. Four random primers, that is, OPA2, OPA3, OPA4 and OPA13, successfully amplified the DNA. The polymorphisms generated by these four primer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The DNeasy Plant Mini Kit was found to be unsuitable for Gracilaria, as it could not efficiently remove the polysaccharide. This was also observed with Sargassum, which has alginic acid (Ho 1995a;Wong et al 2004). This can be overcome by using only the tips of Gracilaria that are freshly ground using liquid nitrogen.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The DNeasy Plant Mini Kit was found to be unsuitable for Gracilaria, as it could not efficiently remove the polysaccharide. This was also observed with Sargassum, which has alginic acid (Ho 1995a;Wong et al 2004). This can be overcome by using only the tips of Gracilaria that are freshly ground using liquid nitrogen.…”
Section: Discussionsupporting
confidence: 58%
“…The random amplified polymorphic DNA (RAPD) assay was successfully used in the classification of seaweeds at the genus and species levels: Gracilaria (González et al 1996;Lim et al 2001), Gelidium species (Patwary et al 1993;Bouza et al 2006), Porphyra (Dutcher and Kapraun 1994;Huh et al 2006), Sargassum species (Ho et al 1995a, b;Wong et al 2004), Hizikia fusiformis (Park et al 1998), Laminaria (Billot et al 1999) and Furcellaria lumbricalis (Valatka et al 2000). Sex-specific markers using RAPDs have been identified in insects (Holloway et al 2000), fish (Iturra et al 1998;Liu et al 1999) and plants (Deputy et al 2002;Lemos et al 2002;Mandolino et al 2002;Xu et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, there has been interest in supplementing traditional systematics of this genus with molecular approaches (Ho et al. 1995a, b, Wong et al. 2004).…”
mentioning
confidence: 99%
“…Although it is unclear whether the material used by Kantachumpoo et al (2015) is the same as that described in Noiraksar & Ajisaka (2008), it is likely that the S. baccularia sensu Kantachumpoo et al (2015) has been misidentified. In Malaysia, Wong et al (2004) also noted the confused taxonomies of S. baccularia and S. polycystum and showed that S. polycystum and S. baccularia can be distinguished based on random amplified polymorphism DNA (RAPD) and morphology. For the latter, they suggested that the absence of secondary holdfasts derived from secondary axes distinguishes S. baccularia from S. polycystum .…”
Section: Discussionmentioning
confidence: 99%